Comparison of Anxiety, Depression and the Quality of Life Between Hemodialysis and Renal Transplantation Patients - ARIKAN, İZZET HAKKI (TURK NEFROLOJI DIYALIZ TRANSPLANTASYON DERGISI, 2017)
OBJECTIVE: This study was designed to compare anxiety, depression and the quality of life in hemodialysis (HD) and renal transplant (Tx) patients. MATERIAL and METHODS: A total of 90 patients (50 HD, 40 Tx) were included in the study. Data was collected using the Beck Anxiety Inventory, Beck Depression Inventory and the SF-36 quality of life scale. Chi-square test, analysis of variance and independent samples t test were used for statistical analysis. RESULTS: Both groups had similar socio-demographic characteristics. There was no significant difference in anxiety and depression scores between the groups (p>0,05). However, anxiety and depression scores were higher in women. There was no correlation between the duration of dialysis treatment with anxiety or depression but the post-transplant time was positively correlated with anxiety and depression. The quality of life sub-scales of physical function, physical role difficulties, role emotional distress, vitality, general health and physical component scores were found lower in the HD group (p<0.05). Quality of life scores were similar in males and females. CONCLUSION: Anxiety and depression scores were similar in HD and renal transplantation patients whereas the quality of life was better in the Tx group.
Keywords: Anxiety; Depression; Hemodialysis; Quality of life; Renal transplantation; DISEASE; HEALTH; INVENTORY; DIALYSIS; ILLNESS